2015
DOI: 10.1161/circulationaha.115.017038
|View full text |Cite
|
Sign up to set email alerts
|

Intramural Ventricular Septal Defect Is a Distinct Clinical Entity Associated With Postoperative Morbidity in Children After Repair of Conotruncal Anomalies

Abstract: Background Intramural ventricular septal defects (VSDs) are interventricular communications through right ventricular free wall trabeculations that can occur after repair of conotruncal anomalies. We assessed the prevalence of residual intramural VSDs and their effect on postoperative course. Methods and Results Children who underwent biventricular repair of a conotruncal anomaly from 1/1/06 to 6/30/13 and had a post-operative transthoracic echocardiogram were included. Images were reviewed for residual intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 14 publications
(23 reference statements)
0
15
0
Order By: Relevance
“…Children with hemodynamically significant intramural VSDs are reported to have a substantially higher rate of postoperative morbidity, mortality, and hospital stays. Intramural VSDs are also reported to be larger than other residual VSDs that might lead to increased clinical sequels [1,2]. The prevalence, risk factors and outcomes of these unusual residual defects are not well defined in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Children with hemodynamically significant intramural VSDs are reported to have a substantially higher rate of postoperative morbidity, mortality, and hospital stays. Intramural VSDs are also reported to be larger than other residual VSDs that might lead to increased clinical sequels [1,2]. The prevalence, risk factors and outcomes of these unusual residual defects are not well defined in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Patel et al, an 11% of studied population were found to have intramural VSDs after repair of conotruncal abnormalities accounting for 19% of residual VSDs. Most of the affected patients had undergone total correction for tetralogy of Fallot as it is the most common type of conotruncal abnormality but a higher incidence in the more complex conotruncal pathologies should be expected [1]. Diagnosis could be far more challenging than other types of residual VSDs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the IVR, with or without enlargement of VSD, carries a high risk for reoperation for VSD residual (or modification of baffle repair) ahead of DORVs or all types of conotruncal abnormalities. 17 We believe this surgical parameter requires a particularly precise surgical management (size and localization of septal resection) to avoid risks in the short term (conduction disorders, residual VSD) and long term (subaortic obstruction). In regard to reoperation for left ventricular outflow obstruction, one may conclude that an aggressive approach with almost routine VSD enlargement may decrease late left ventricular outflow obstruction.…”
Section: Outcomes According To Anatomic Characteristicsmentioning
confidence: 99%